The Role of Lifestyle and Personal Characteristics on Fear of Victimization among University Students - Lee, Daniel R. (American journal of criminal justice, 2012)
The fear of crime has been both theoretically and empirically connected to a complex relationship of situational context (e.g., time of day, location) and personal characteristics (e.g., age, race, gender, personal and vicarious victimization). Building off of routine activities and lifestyle-exposure theory, this research extends the understanding of these relationships by examining the impact of lifestyle activities (e.g., consumption of alcohol, illicit drugs, and time away from residence) and personal characteristics (e.g., direct and vicarious victimization) on the fear of various crimes across temporal situations, among a sample of college and university students. The results indicate that fear of crime varies by crime type and that certain demographic and lifestyle characteristics and experiences with victimization affect students’ fear of crime. Although no evidence was found to suggest that fear of theft varies by temporal context (i.e., during the day or at night), certain characteristics, such as gender, perceived risk, and avoidance behaviors, have varying relationships with fear of violent crimes when considering time of day. The findings suggest that future research should examine more critically the relationship that lifestyles, personality, gender, and time of day have with the fear of crime.